Web-based sale and purchase online product catalogue and ordering system (OPCOS) / Lee Wai Lin - Lee , Wai Lin (2003)
Web-based sale and purchase is the buying and selling of goods and services on the Internet, especially the World Wide Web. It makes purchasing easier for customer. However, it will cost a corporation a lot of money to build up a dynamic eCommerce website. To overcome this issue, a web-based sale and purchase is developed to create web page to selling the corporation 's products. The proposed project offers a web-based service to let suppliers put their products to sell online. In the meantime, this allows the customers to have more choices in same products and enables to compare the prices in the same web page. It includes online product catalogue, online ordering system, backend management and database. The dynamic database is hooked up to the existing back end system for order fulfillment (front-end) and member registration process (front-end) The aim of this project - Online Product Catalogue and Ordering System (OPCOS) is to develop and design the e-commerce application for a product catalogue, shopping cart and ordering system. This project also define the objectives, scope, problems and tools to use that should be identified before the development of this system. Several research and case study had done to d assessment and review about the system. Waterfall Model with prototyping is used as a methodology of the proposed project. Three-tier client/server architecture will be implemented to model the system architecture. In addition. Online Product Catalogue and Ordering System (OPCOS) is planned to be developed by using Hypertext Predecessor (PHP) and Apache Web Server on the Microsoft Windows 200 Server platform utilizing database created using MySQL.The system design is dynamic and supporting concurrent users to interact with the system over Internet. Finally, the intended Online Product Catalogued and Ordering System (OPCOS) Should able to produce the web pages that allow users to do online shopping and order their desired products. A database also has to be implemented for storing data that would be retrieved for display and captured from users.